Multi-Axis Resonant Filter Design using Frequency Response Data applied to Industrial Scan Stage - Mae, Masahiro; Ohnishi, Wataru; Fujimoto, Hiroshi; Sakata, Koichi (IEEE/ASME transactions on mechatronics, 2024)
Disturbance rejection of the high-precision scan stages is important in industrial lithography equipment. The aim of this article is to develop an optimization method for designing multi-axis resonant filters, that enhance the disturbance rejection performance in scanning motion. The developed optimization method explicitly defines resonant filters in structured representation and formulates the data-driven convex optimization problem. The method enables the multi-axis resonant filter design with iterative convex optimization using the frequency response data of the six-degree-of-freedom experimental setup. Experimental results on the industrial large-scale high-precision scan stage demonstrate the performance improvement of the disturbance rejection in the scanning motion using the optimized resonant filters.